Spatial analysis of tuberculosis cases diffusion based on population density in Bekasi Regency in 2017-2021 - Inggarputri, Yuanita Rizky; Trihandini, Indang; Novitasari, Prihatini Dini; Makful, Martya Rahmaniati (Universitas Gadjah Mada, 2023)
Purpose: This research aims to examine the spatial relationship between tuberculosis cases and population density and their spatial diffusion patterns in Bekasi Regency in 2017-2021. Methods: Research using an ecological study design using spatial analysis to estimate and analyze the distribution of tuberculosis prevalence related to population density in 23 sub-districts in Bekasi Regency, compare data from 2017 to 2021 and evaluate the spatial correlation. The data is taken from secondary data from the Bekasi District Health Office for 2017-2021. Results: This study shows a spatial autocorrelation between tuberculosis cases and population density from 2017 to 2021 (I>E; p-value <0,05). There is spatial diffusion of cases characterized by expanding clusters with high tuberculosis cases. High-high cluster in 2017, there was one sub-district. In 2018 there was also one sub-district. In 2019 there were two sub-districts. In 2020, there were three sub-districts. And in 2021, there were five districts. Conclusion: This research shows a positive spatial autocorrelation in the incidence, which is influenced by population density in Bekasi Regency from year to year (2017-2021) with a clustering pattern.